COMPETÊNCIAS ESSENCIAIS DOS GESTORES ADMINISTRATIVOS E DE APOIO DE UMA UNIVERSIDADE COMUNITÁRIA: O CASO DA UNIJUÍ - ABREU, ROSELI L.; SILVA, VIVIAN R. D.; TEIXEIRA, ENISE B. (Salão do Conhecimento, 2013)
Resumo